Pengaruh Social Media Marketing Instagram dan Electronic Word of Mouth terhadap Purchase Intention - Pahrul Albi Suhara; Dwi Mulyaningsih, Hendrati; Dwi Nugraha , Yudha (Bandung Conference Series: Business and Management, 2024)
Abstract. This research focuses on the variables of social media marketing, electronic word of mouth and purchase intention. This research aims to test and find out how social media marketing and electronic word of mouth influence purchase intention among Russ & Co Instagram consumers. in Bandung City. This research is included in the type of descriptive and verification research with quantitative methods. The sampling technique used is nonprobability sampling, namely purposive sampling. The data collection method used in this research is a survey method with a questionnaire instrument. The objects of this research are Russ & Co consumers. Instagram users who live in Bandung City and follow or follow Instagram Russ & Co. with a total of 160 respondents who were narrowed down again based on sampling criteria to 150 respondents. The data analysis used is descriptive and verification analysis, namely by using multiple linear regression analysis, T test, F test, and coefficient of determination. The results of this research show that social media marketing partially has a positive and significant effect on purchase intention, electronic word of mouth has a positive and significant effect on purchase intention. Then simultaneously social media marketing and electronic word of mouth have a positive and significant effect on purchase intention. Abstrak. Penelitian ini berfokus pada variabel social media marketing, electronic word of mouth dan purchase intention. Penelitian ini bertujuan untuk menguji dan mengetahui bagaimana pengaruh social media marketing dan electronic word of mouth terhadap purchase intention pada konsumen Instagram Russ & Co. di Kota Bandung. Penelitian ini termasuk ke dalam jenis penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu purposive sampling. Metode pengumpulan data yang digunakan dalam penelitian ini yakni metode survey dengan instrument kuesioner. Objek pada penelitian ini adalah konsumen Russ & Co. pengguna Instagram yang berdomisili di Kota Bandung dan mengikuti atau mem-follow Instagram Russ & Co. dengan jumlah 160 responden yang dikerucutkan Kembali berdasarkan kriteria sampling menjadi 150 responden. Analisis data yang digunakan adalah analisis deskriptif dan verifikatif yaitu dengan menggunakan analisis regresi linier berganda, uji T, uji F, dan koefisien determinasi. Hasil penelitian ini menunjukkan bahwa social media marketing secara parsial berpengaruh positif dan signifikan terhadap purchase intention, electronic word of mouth berpengaruh positif dan signifikan terhadap purchase intention. Kemudian secara simultan social media marketing dan electronic word of mouth berpengaruh positif dan signifikan terhadap purchase intention